Measurement of spontaneous platelet aggregation in patients with acute cerebral infarction using laser-scattered light aggregometry - Sugihara, Hiroshi; Yazaki, Naoko; Toshima, Hiroko; Yamada, Koji; Hirayama, Toshikazu; Takahashi, Youichi (Japanese Journal of Stroke, 2004)
Quantitative analysis of platelet aggregation is difficult, and the conditions of platelet aggregation in patients with acute cerebral infarction have not previously been examined in sufficient detail. We quantitated the spontaneous platelet aggregation (SPA) in patients with acute cerebral infarction using laser-scattered light aggregometry. The subjects comprised 98 patients with acute cerebral infarction. The subtype diagnoses included atherothrombotic infarction (ATI ; n = 45), lacunar infarction (LI ; n = 21) and cardioembolic in. farction (CE; n=32).The SPA was evaluated on days 1, 3, 7, 14 and 28 after the onset of cerebral infarction.The serum lipid, plasma glucose and diastolic blood pressure levels were relevant to the SPA after the onset of cerebral infarction. The maximum SPA was significantly increased in the patients with ATI and CE as compared to those with LI. No significant changes in SPA were recognized during the acute stage of cerebral infarction in cases of ATI or LI. The SPA on day 3 was significantly increased as compared to that on day 14 in CE. These findings suggest that activation of SPA differs among patients with different subtypes of cerebral infarction, and the SPA represents a useful marker of platelet activation.